HOW QUALITY, VALUE AND SATISFACTION CREATE PASSENGER LOYALTY: AN EMPIRICAL STUDY ON INDONESIA BUS RAPID TRANSIT PASSENGER - Hussein, Ananda Sabil; Hapsari, Raditha (The International Journal of Accounting and Business Society, 2014)
This study aims to investigate the dimensions of service quality especially in the area of public transport as well asthe role of service quality in enhancing passenger’s value, satisfaction and loyalty. Partial Least Squares (PLS) with survey data from 152 BRT passengerswas used by this study. This study found that outcome quality, physical quality and interaction quality are the the primary dimensions of service quality. In addition, this study explained that service quality has a signifiant effect on passenger perceived value, satisfaction and loyalty. Apart from perceived service quality, this study also found that passenger satisfaction and perceived value are the essential determinants of passenger loyalty.Keywords: Bus Rapid Transit, Outcome quality, Interaction quality, Physical quality, service quality, satisfaction and loyalty.